Evaluasi Strategi SERVO Analysis Terhadap Kinerja CV. Rafiza Chicken Indonesia - Syahrudi Syahrudi; Prasetio Ariwibowo; Abdul Azim Wahbi (Sosio e-Kons, 2022)
This study aims to identify business development strategies and evaluate business development strategies using analysis. and identify the achievement of the concept of fit in the CV business development strategy. Rafiza Chicken Group Indonesia. This research belongs to the type of descriptive research. The object of research is business development strategy and evaluation of CV's business development strategy. Rafiza Chicken Group Indonesia. This study uses purposive sampling of top management, Then followed by the snowball sampling technique. The type of research data is qualitative data, which is collected through interviews, observations, and document analysis. This study uses the SERVO analysis approach to evaluate the company's business strategy, and how to implement the company's strategy. SERVO Analysis itself has 5 components, namely Strategy, Environment, Resource, Value, and Organization. Test the validity of the data using source triangulation, while data analysis using qualitative data analysis. From the results of the evaluation of business strategy on the CV. Rafiza Chicken Indonesia, it is concluded that CV. Rafiza Chicken Indonesia uses a differentiation strategy and customer behavior oriented, where through the uniqueness and differences of products that follow market tastes (consumers and prospective franchisees) with competing products, the company produces products that are unique and always different, and have many variants. The strategy in the CV. Rafiza Chicken Indonesia is in accordance with the existing local fried chicken industry, and its implementation is also correct. But judging from the company's vision and goals, in developing and expanding the market to all other corners of Indonesia, the company has obstacles that can hinder CV's vision. Rafiza Chicken Indonesia. Based on the results of SERVO analysis, it was found that the company experienced obstacles in terms of resources and organization.